Improving Elementary School Students Communication Skills Through The Scramble Model - wildaniah, Ragil; Siti Anisah, Ani; Akmal, Rudi (Cahaya Smart Nusantara, 2023)
The background to this problem is reality that communication skills are still relatively low due to the lack of learning models and methods that are interesting and capable of active interaction. The aim of this research is to find out how effective it is and how to improve students' communication skills after using the scramble type cooperative learning model. The design used in this research is Pre with the form of an experimental design (Intac-Group Comparison), where this research was carried out in one class and divided into two. The instruments used in the research to collect data were observation sheets, oral and written tests to measure students' communication skills. Data collection was carried out twice, namely before and after treatment was given, to see the increase in students' communication skills. The results of this study stated that communication skills after implementing the scramble type cooperative learning model were stated to be very good with results from the first and second observation sheets with a score of 89%. The results of the hypothesis test showed that the t count was 7.948 > from the t table 2.021. So it can be concluded that Ha is accepted and Ho is rejected. This means that there are differences in students' communication skills. The N-Gain test results for the experimental class obtained a result of 0.74, which means 74% and has a moderate interpretation, while the control class got a result of 0.63, which means 63%. The results of the effectiveness test with effective interpretation, so it can be concluded that the scramble type cooperative learning model can improve students' communication skills.